Lokasi Pengesan Dan Sudut Penghadang Optimum Untuk Tomografi Kemuatan Elektrik Bagi Penganggaran Ketinggian Minyak - Ibrahim, Ahmad Kamal (Universiti Sains Malaysia, 2006)
Electric capacitance tomography (ECT) is one of the branches of process tomography that applied in imaging sector. ECT is one of the techniques to measure the internal spatial of materials. Artificial Neural Network (ANN) is an electronic model that designed from human brain to process information that use learning algorithm. ECT is a process that uses capacitance for determine of certain values. There are two types of tomography systems; one is medical tomography and process tomography. The importance of this research is to determine the pipe thickness, R2 and the of electrode guard angle, βº. This process done is to get the optimum parameter which is the lowest mean of absolute error. Matlab is used to generate raw ECT dataset with using an ECT simulator.